Coastal Evolution Late Quaternary Shoreline Morphodynamics. - Carter, R. W.; Woodroffe, C. D.; Van de Plassche, Orson; Van de Plassche, Orson (Cambridge University Press, 1997)
Annotation This book assesses how coastlines change and how they have evolved over the past few thousand years. It introduces some of the latest concepts in coastal morphodynamics, recognizing that coasts develop through co-adjustment of process and form. The authors examine particular types of coasts--deltas, estuaries, reefs, lagoons and polar coasts--in detail with conceptual models developed on the basis of well-studied examples. In addition to being a text for graduate-level students, this is a comprehensive source for geologists, engineers, environmental scientists, planners and coastal managers.
Keywords: elektronické knihy; electronic books